2011
DOI: 10.1051/0004-6361/201116781
|View full text |Cite
|
Sign up to set email alerts
|

Deep wide-field near-infrared survey of the Carina Nebula

Abstract: Context. The Great Nebula in Carina is a giant H ii region and a superb location in which to study the physics of violent massive star formation, but the population of the young low-mass stars remained very poorly studied until recently. Aims. Our aim was to produce a near-infrared survey that is deep enough to detect the full low-mass stellar population (i.e. down to ≈0.1 M and for extinctions up to A V ≈ 15 mag) and wide enough to cover all important parts of the Carina Nebula complex (CNC), including the cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 87 publications
8
101
0
Order By: Relevance
“…We note that Lada et al (2010) have demonstrated a good correlation between the gas mass above A V > 7 and the star formation rate, that seems to be valid over a very wide range of cloud masses. This relation predicts a star formation rate of the order 10 −3 M yr −1 for the CNC, which is well consistent with the integrated mass and age distribution of the young stars that have formed recently in these clouds (see Preibisch et al 2011c).…”
Section: Conclusion and Summarysupporting
confidence: 82%
See 3 more Smart Citations
“…We note that Lada et al (2010) have demonstrated a good correlation between the gas mass above A V > 7 and the star formation rate, that seems to be valid over a very wide range of cloud masses. This relation predicts a star formation rate of the order 10 −3 M yr −1 for the CNC, which is well consistent with the integrated mass and age distribution of the young stars that have formed recently in these clouds (see Preibisch et al 2011c).…”
Section: Conclusion and Summarysupporting
confidence: 82%
“…We note that this region contains the cluster Tr 15 and Bo 10, which have estimated ages of 7−8 Myr (Dias et al 2002;Preibisch et al 2011c) and are thus several Myr older than the clusters Tr 14 and Tr 16 in the center of the Carina Nebula. This could suggest that at this older age, the stellar-wind feedback (especially from the evolved massive stars) may play an important role.…”
Section: Bubbles North Of η Car (Nb)mentioning
confidence: 77%
See 2 more Smart Citations
“…The near-infrared data presented in this paper were obtained in the context of our large survey of the Carina Nebula (see Preibisch et al 2011c, for more details) with the instrument HAWK-I (see Kissler-Patig et al 2008) at the ESO 8 m Very Large Telescope. HAWK-I is equipped with a mosaic of four Hawaii 2RG 2048 × 2048 pixel detectors with a scale of 0.106 per pixel.…”
Section: Observationsmentioning
confidence: 99%